Finite element analysis of composite materials with Abaqus - Barbero, Ever J. (Boca Raton, FL CRC Press,Taylor & Francis Group, 2013)
'Completely revised and updated, this book is a new version of Finite Element Analysis of Composite Materials with worked examples rewritten in Abaqus software instead of ANSYS. Based on one of the best-known textbooks on finite element analysis of composite materials, it reflects the state of the art in modeling. The original book will also be updated but will provide ANSYS problems'--
'Preface Finite Element Analysis of Composite Materials deals with the analysis of structures made of composite materials, also called composites. The analysis of composites treated in this textbook includes the analysis of the material itself, at the micro-level, and the analysis of structures made of composite materials. This textbook evolved from the class notes of MAE 646 Advanced Mechanics of Composite Materials that I teach as a graduate course at West Virginia University. Although this is also a textbook on advanced mechanics of composite materials, the use of the finite element method is essential for the solution of the complex boundary value problems encountered in the advanced analysis of composites, and thus the title of the book. There are a number of good textbooks on advanced mechanics of composite materials, but none carries the theory to a practical level by actually solving problems, as it is done in this textbook. Some books devoted exclusively to finite element analysis include some examples about modeling composites but fall quite short of dealing with the actual analysis and design issues of composite materials and composite structures. This textbook includes an explanation of the concepts involved in the detailed analysis of composites, a sound explanation of the mechanics needed to translate those concepts into a mathematical representation of the physical reality, and a detailed explanation of the solution of the resulting boundary value problems by using commercial Finite Element Analysis software such as AbaqusTM. Furthermore, this textbook includes more than fifty fully developed examples interspersed with the theory, as well as more than seventy-five exercises at the end of chapters, and more than fifty separate pieces of Abaqus'--
Includes bibliographical references (pages 395-406) and index.
Keywords: Composite materials -- Mathematical models; Finite element method